Has recent economic growth/recession in Brazil been pro-poor?. Issue 15 (2nd September 2021) - Wang, Zuobao; Sun, Jing
ABSTRACT: This paper evaluates whether recent economic growth/recession in Brazil was pro-poor during the period of 2006–2016 and compares the boom and recession periods. The results show that in boom periods, the growth in Brazil is pro-poor but not pro-ultrapoor. While the recession is anti-poor especially anti-ultrapoor and such worsened inequality dominates the increasing trend of poverty in Brazil.